A multi-sample analysis method with spatial resolution based on a single-longitudinal-mode fiber optofluidic microring laser. (June 2021) - Shi, Huimin; Guo, Huiyi; Yu, Jie; Wang, Zhi; Liu, Xiaoqi; Liu, Yan-ge
Highlights: A multi-sample analysis method based on a fiber optofluidic laser is proposed. The continuous analysis is realized only by introducing spatial resolution. The method has a high lasing intensity sensitivity of 303a.u./μM. Abstract: A multi-sample analysis method with spatial resolution based on a single-longitudinal-mode fiber optofluidic microring laser is proposed and experimentally demonstrated. Spatial resolution is introduced into micro-fluid control system of the single-longitudinal-mode optofluidic laser, in which a hexagonal silica ring inside a simplified hollow-core microstructured optical fiber is used as the resonator. By monitoring the power change of the single longitudinal mode lasing generated by the side pumping, continuous detection and analysis for multiple samples can be realized quickly and efficiently. With this method, the influence of Rhodamine B solution with different concentration on the single-longitudinal-mode fiber optofluidic laser designed by mixing 1 mM Rhodamine 6G is investigated experimentally. The experimental results show that the proposed multi-sample analysis method can clearly distinguish the Rhodamine B solution from 0.08 mM to 0.13 mM, with a high lasing intensity sensitivity of 303 a.u./μM. Moreover, due to the introduction of energy resonance transfer effect, the minimum excitation concentration of Rhodamine B is reduced from 270 µM to 45 µM. Increase the concentration of Rhodamine 6G to 2 mM, laser-based sensing for the concentration of Rhodamine B can still be achieved, and the minimum excitation concentration can be further reduced to 15 µM. This work provides possibilities for laser-based biochemical analysis with multi-sample, high throughput and high sensitivity.